Constituição da identidade docente na trajetória de professores de ciências da natureza que atuam por meio da pesquisa em sala de aula - Thomaz, Estrella Marlene da Silva (2022)
In the globalized world, the complexity of subjective and objective trajectories involved in the constitution of identities requires thinking about how the subject of today suffers experiences and experiences the diversity of cultural influences in which he is immersed. In this context, the figure of the teacher was chosen as an object of study, to know how this complexity of processes permeates the constitution of their teaching identity, especially when their actions are associated with teaching through research as an educational principle. Thus, this investigation is related to teaching, the attitudes of teachers, and their positions in the classroom and the way they teach, believing that this position is directly related to the process of constituting their identity, which, in turn, is result of the appropriation of historically constructed meanings. Consequently, the investigation aims to understand the process of constitution of the teaching identity of professors who work in the area of Natural Sciences, with a view to their performance in the classroom, through research actions. In this investigation, the use of Oral Histories (OH) offered a possibility of understanding, through the testimonies of two professors, who work through research in their teaching activities, the factors that influenced and have influenced the constitution of their professional identity. The corpus of analysis was constituted by the reports of facts and decisive experiences about the life trajectory of these professionals. In the analytical treatment of information, the production of meanings took place through the analysis of discursive practices based on Mary Jane Spink (2000, 2004). According to the author, it is necessary to understand how individual thinking is rooted in the social and how one and the other are mutually affected. The autobiographical reports contributed to the understanding that the process of teacher identity can be raised from the first years of socialization with important theoretical and practical knowledge, regarding the affective dimension intrinsic to the process of teacher constitution.